Preventing epileptogenesis by interaction between inositol isomers and proteins - Lia Tsverava; Luka Kharkhelauri; Vincenzo Lagani; Giorgi Gamkrelidze; Veriko Bokuchava; Tamar Kiguradze; Merab Kokaia; Revaz Solomonia (Epilepsia Open)
Abstract Objective Inositols play significant roles in biological systems. Myo‐inositol (MI), the most prevalent isomer, functions as an osmolyte and mediates cell signal transduction. Other notable isomers include Scyllo‐inositol (SCI) and D‐Chiro‐inositol (DCHI). Our previous investigations have highlighted MI's potential antiepileptogenic effects, although its exact mechanisms of action during epileptogenesis remain unclear. A critical, unexplored area is how inositols interact with proteins. Additionally, the antiepileptogenic capabilities of SCI and DCHI have yet to be determined. This study seeks to address these gaps. Methods Inositol interacting proteins were identified by cellular thermal shift assay. Status epilepticus (SE) in rats was induced using kainic acid (KA), followed by a 28‐day treatment with either MI, SCI, DCHI, or saline. The duration and frequencies of behavioral spontaneous recurrent seizures (SRS) were scored for 8 weeks by 24 h video monitoring system. The effects of inositol treatment on spatial learning and memory deficits associated with epileptogenesis were evaluated by Morris water maze test. The changes in protein amounts were studied by Western immunoblotting. Results We identified several proteins that interact with inositols, noting both commonalities and isomer‐specific associations. For the first time, we demonstrated that the treatment with SCI and DCHI, alongside MI, significantly reduces the frequency and duration of behavioral SRS in a KA‐induced post‐status epilepsy model in rats. This reduction persisted for 4 weeks post‐treatment. Moreover, all three inositol isomers mitigated spatial learning and memory deficits associated with epileptogenesis. Alterations in the inositol interacting proteins: alpha synuclein and 14‐3‐3 theta were further examined 8 weeks post‐SE in the hippocampus and neocortex of rats. Significance Myo‐inositol, SCI and DCHI interact with a number of proteins involved in different biological pathways. All studied inositol isomers express long‐term beneficial effects on KA‐induced SRS and the associated comorbidities. Inositols can be successfully used in the future for translational research. Plain Language Summary Epilepsy is a common neurological disorder characterized by spontaneous recurrent seizures and a range of associated comorbidities. The process that leads to the development of epilepsy is called epileptogenesis, and currently, no medication can effectively prevent it. Our study investigated the effects of a group of compounds—myo‐inositol, scyllo‐inositol, and D‐chiro‐inositol—that have potential antiepileptogenic properties on epilepsy induced by kainic acid. We found that: (i) the three inositol isomers share some common target proteins and also have unique ones and (ii) all of them counteract epileptogenesis and the related cognitive impairments.